Effects of Tiktok English Teaching Videos in The Second Language Acquisition of Elementary Learners - Shaina Mae S. De Matta; Xamiela A. Ibaite; Noreen Ann S. Revistual; Dan Fereth Fajardo (DIALEKTIKA: JURNAL BAHASA, SASTRA DAN BUDAYA, 2023)
This study aimed to examine the Effects of TikTok English teaching videos in the Second Language Acquisition of Elementary Learners. The participants of this study were the 21 intermediate learners in Nababarera Elementary School, Baao, Camarines Sur. The researchers came up with the three main questions in this study: (1) What is the level of Second Language Acquisition of elementary learners during: a. Pre-Assessment b. Post-Assessment (2) Is there a significant difference between the raw scores of pre-assessment and post-assessment? (3) What are the challenges encountered in utilizing mobile phones as a tool for second language acquisition? The researchers used mixed-method approach to answer the research questions. A pre- and post-assessment and a semi-structured interview were used as tools. It is discovered that learners who use mobile devices for language learning experience learning setbacks due to physical, pedagogical, and psycho-social issues. The result also showed that there is a significant difference between the raw scores of the learners’ pre- and post-assessment. Hence, TikTok can be an assessment tool for evaluating learners' language learning progress and an out-of-class learning tool to motivate and engage students in their English language skills development.